Will growing invasive arthropod biodiversity outpace our ability for eradication?. Issue 8 (28th August 2019) - Suckling, David M.; Stringer, Lloyd D.; Baird, David B.; Kean, John M.
Abstract: The Global Eradication Database documents 811 eradication attempts against invasive arthropods since 1890, in 104 countries. Eradication programs show a greater than exponential increase in the number of programs started in recent decades. In addition, there is a trend of a rapidly diversifying burden of the most severe threats. The species richness showed a three‐fold increase in number of species under eradication in the last 50 yr, and all taxonomic levels rose dramatically. The increase in number of eradication programs shows that current management measures for constraining the spread of invasive species are inadequate. A similar surge in the number of governments trying to prevent the establishment of new pests has occurred. Increased biodiversity of arthropod eradication targets includes new pest groups with fewer tools developed for management. We argue that a rapid increase in biodiversity of invasive and economically or environmentally damaging organisms represents a substantial and underestimated challenge for managers wanting to prevent their establishment, requiring a shift in research focus to accelerate delimitation and suppression options with less reliance on insecticides.